Matrices and Scaffolds for DNA Delivery in Tissue Engineering - De Laporte, Laura (2007)
Regenerative medicine aims to create functional tissue replacements, typically through creating a controlled environment that promotes and directs the differentiation of stem or progenitor cells, either endogenous or transplanted. Scaffolds serve a central role in many strategies by providing the means to control the local environment. Gene delivery from the scaffold represents a versatile approach to manipulating the local environment for directing cell function. Research at the interface of biomaterials, gene therapy, and drug delivery has identified several design parameters for the vector and the biomaterial scaffold that must be satisfied. Progress has been made towards achieving gene delivery within a tissue engineering scaffold, though the design principles for the materials and vectors that produce efficient delivery require further development. Nevertheless, these advances in obtaining transgene expression with the scaffold have created opportunities to develop greater control of either delivery or expression and to identify the best practices for promoting tissue formation. Strategies to achieve controlled localized expression within the tissue engineering scaffold will have broad application to the regeneration of many tissues, with great promise for clinical therapies.